2017
DOI: 10.4149/neo_2017_420
|View full text |Cite
|
Sign up to set email alerts
|

High Farnesoid X Receptor (FXR) expression is a strong and independent prognosticator in invasive breast carcinoma

Abstract: Farnesoid X Receptor (FXR), a nuclear receptor superfamily member, is related with bile acids, glucose and lipids metabolism and recently with cancer. In the present study the clinical significance of FXR expression in invasive breast carcinoma was evaluated. FXR protein expression was assessed immunohistochemically on paraffin-embedded breast cancer tissues obtained from 115 breast cancer patients and was statistically analyzed with clinicopathological parameters, estrogen receptor (ER), progesterone receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 31 publications
2
24
0
1
Order By: Relevance
“…As a general finding, FXR signaling in these cell lines led to oncosuppressive effects (27,44,45). Consistent with these observations, high FXR expression in human breast tumors was associated with favorable patient survival in one analysis (46). These data further substantiate our findings that the tumor bile acid content associates with a less aggressive disease and improved patient survival in breast cancer.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As a general finding, FXR signaling in these cell lines led to oncosuppressive effects (27,44,45). Consistent with these observations, high FXR expression in human breast tumors was associated with favorable patient survival in one analysis (46). These data further substantiate our findings that the tumor bile acid content associates with a less aggressive disease and improved patient survival in breast cancer.…”
Section: Discussionsupporting
confidence: 88%
“…S8). Other studies have shown FXR protein expression in these cell lines and tumors using Western blot analysis and IHC (27,(44)(45)(46). As a general finding, FXR signaling in these cell lines led to oncosuppressive effects (27,44,45).…”
Section: Discussionmentioning
confidence: 66%
“…188,189 High FXR associated with smaller tumor size, high proliferation rate, relapse-free survival, distant metastasis-free survival, and overall survival in BC patients. 190,191 Indeed, FXR is an independent prognostic factor for overall and disease-free patients' survival. 191 Potential mechanisms of action include FXR-mediated inhibition of leptin-induced oncogenic cancer-associated fibroblasts (CAFs) in multiple BC cell lines by increasing suppressor of the cytokine signaling 3 (SOCS3) expression downstream of FXR-implicating an obesity-specific susceptibility.…”
Section: Can Bas Also Influence Bc? the Presence Of Bas In Breast Tissuementioning
confidence: 99%
“…190,191 Indeed, FXR is an independent prognostic factor for overall and disease-free patients' survival. 191 Potential mechanisms of action include FXR-mediated inhibition of leptin-induced oncogenic cancer-associated fibroblasts (CAFs) in multiple BC cell lines by increasing suppressor of the cytokine signaling 3 (SOCS3) expression downstream of FXR-implicating an obesity-specific susceptibility. 188 SOCS3 is downregulated in BC.…”
Section: Can Bas Also Influence Bc? the Presence Of Bas In Breast Tissuementioning
confidence: 99%
“…Вариации уровня miR-194 в опу-холях одного происхождения коррелируют со стадией ракового заболевания, с чувствительностью опухолей к терапии и с прогнозом [38][39][40]. Поскольку снижение уровня miR-194 может быть ассоциировано с увеличе-нием экспрессии FXR, представленность данного рецеп-тора может быть полезным прогностическим признаком не только для НАЖБП и связанных с ней патологий пе-чени, но и для раковых заболеваний различного проис-хождения [41][42][43].…”
Section: не только нажбп: роль Fxr в онкогенных процессахunclassified